Penyusunan Standar Operasional Prosedur (SOP) Penggunaan Ruang Baca Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Pattimura - Titahena, Merlyn; Rumalean, Iwan (Universitas Pattimura, 2025)
The need for optimal use of reading rooms in academic environments requires orderly, systematic management that is oriented towards user needs. In the Indonesian Language and Literature Study Program at the Indonesian Literature Program at Pattimura University, the absence of Standard Operating Procedures (SOPs) has resulted in ineffective use of the reading room, characterized by irregularities in borrowing and storing reading materials, as well as underutilization of available facilities. Therefore, this community service activity aims to develop and implement SOPs for the use of reading rooms as a strategic step to improve efficiency, comfort, and regularity in academic activities. The activity process was carried out in several stages, namely identifying user needs through surveys and observations, developing SOPs based on data analysis results, disseminating new rules through print and digital media, and evaluating the effectiveness of their implementation. The results of the implementation show a significant increase in the orderliness of the reading room's use, users' understanding of the rules, and the efficiency of facility management. Thus, the development and implementation of SOPs not only create a more conducive academic environment but also encourage a culture of literacy and shared responsibility in maintaining learning facilities that support the improvement of education quality on campus.